Efeitos da regulação do nível hidrométrico sobre a dinâmica temporal de espectros de tamanho de peixes de um reservatório neotropical. - Fernandes, Rodrigo (2009)
In this study we investigated the dynamics of fish size spectra along the process of formation of the Corumbá Reservoir, Brazil. The main objectives were to evaluate the influence of the filling stage and dam operation on the temporal variability of the slopes of fish size spectra. In addition, we explored the relationships between the temporal variability of the slopes of size spectra and the average water level and rainfall. For this, the fish assemblages were monthly collected from March 1996 to February 2000, covering a period before regulation, the entire filling stage and a further period influenced by the dam operation. To calculate the slopes of fish size spectra we used Pareto I model. To model the dynamics of time series with the slopes of size spectra and evaluate the effects of the filling stage and dam operation we applied, respectively, ARIMA models and intervention analysis. To evaluate the effects of average water level and rainfall variability on the slopes of size spectra we used cross-correlation functions. The slopes of size spectra showed a high temporal variability. The filling stage produced a change of 143% over the previous period, along with a significant increase in fish size classes between 4 and 15.9 g. After the filling stage, the slopes and BPUE of most size classes increased gradually until the end of the study. The slopes were negatively related with the average water level and rainfall variability. The results presented in this paper showed that the distribution of individual size, during the filling stage and dam operation, drastically suffered the combined effects of stochastic events (water level regulation by the dam) and seasonal variations in ecosystem productivity.